2019
DOI: 10.1111/1755-6724.13765
|View full text |Cite
|
Sign up to set email alerts
|

The Hizeh‐Jan Kaolin Deposit of NW Iran: the Tetrad Effect in REE Distribution Patterns

Abstract: The Hizeh‐Jan kaolin deposit (northwest of Varzeghan, East‐Azarbaidjan Province, NW Iran) is a product of the alteration of Eocene andesitic rocks. Based on mineralogical examinations, kaolinite, quartz, smectite, pyrophyllite, muscovite‐illite, alunite, calcite, diaspore, goethite and hematite are the most abundant mineral phases in this deposit. The geochemical indicators, such as Y/Ho and Zr/Hf, indicate the non‐CHARAC (non‐Charge‐radius control) behavior of these pairs, which are likely to be due to the oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Based on the recent works, the form of tetrad effect-bearing normalized REE curves can be categorized into four groups [Abedini and Rezaei Azizi, 2019, Abedini et al, 2019b, Feng et al, 2014, Minamim et al, 1998, Nardi et al, 2012: (1) concave or W-type indicative for low temperature deposits, (2) convex or M-type generally occur in magmatic or related systems, (3) conjugate convex-concave or W-M-type and finally (4) zigzag pattern, which can be related to incomplete occurrence of tetrad effect. Previous studies have proposed some quantum mechanical based mechanisms for the occurrence of tetrad effect such as nephelauxetic ratios, the spin energy for coupling, electron configuration of lanthanides and Gibbs free energy [Jorgensen, 1970, Kawabe et al, 1999, Masuda et al, 1994, Nugent, 1970.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the recent works, the form of tetrad effect-bearing normalized REE curves can be categorized into four groups [Abedini and Rezaei Azizi, 2019, Abedini et al, 2019b, Feng et al, 2014, Minamim et al, 1998, Nardi et al, 2012: (1) concave or W-type indicative for low temperature deposits, (2) convex or M-type generally occur in magmatic or related systems, (3) conjugate convex-concave or W-M-type and finally (4) zigzag pattern, which can be related to incomplete occurrence of tetrad effect. Previous studies have proposed some quantum mechanical based mechanisms for the occurrence of tetrad effect such as nephelauxetic ratios, the spin energy for coupling, electron configuration of lanthanides and Gibbs free energy [Jorgensen, 1970, Kawabe et al, 1999, Masuda et al, 1994, Nugent, 1970.…”
Section: Introductionmentioning
confidence: 99%
“…The data processing of the world geological community in relation to kaolin deposits in Russian Federation , Nigeria , China , Iran Abedini, Rezaei Azizi, 2019), Ethiopia , Algeria , South Africa , Malaysia , Cameroon (Nzeukou Nzeugang et al, 2018), Turkey , Egypt . ), Japan showed that the kaolin ores of the Pologivskiy deposit have higher geological and economic indicators, the study of which is a further goal for the authors research.…”
mentioning
confidence: 99%